Reconstruction of the Necrotic Scrotum with Hydrosurgery System and Pedicle DIEP Flap: A Case Report of Fournier Gangrene - Makino, Yuma (Plast Reconstr Surg Glob Open, 2020)
Despite medical advances, the mortality rate associated with Fournier gangrene has remained largely unchanged and extremely high. In addition, conventional surgical treatment of Fournier gangrene of the scrotum requires excision of the testicles in some cases, which can result in loss of fertility. We report herein the favorable results of reconstruction of the scrotum following Fournier gangrene, using the hydrosurgery system and pedicled deep inferior epigastric perforator flap. A 60-year-old male patient was urgently transported to our hospital for fever, lower abdominal pain, and scrotal pain for several days. He was diagnosed with Fournier gangrene and underwent an emergency debridement procedure on the same day. Later, we performed a 2-phase reconstruction with a hydrosurgery system and pedicled deep inferior epigastric perforator flap under general anesthesia for the postoperative tissue defect. At 6 months postoperatively, there was no ulceration or scar contracture, and the results were aesthetically pleasing. There are no reported cases of reconstruction of the scrotum following Fournier gangrene using this procedure, and it might be an effective treatment option.